Opposing effects of 25‐hydroxy‐ and 1α, 25‐dihydroxy‐vitamin D3 on pro‐cachectic cytokine‐and cancer conditioned medium‐induced atrophy in C2C12 myotubes. (19th March 2019) - Sustova, Hana; De Feudis, Marilisa; Reano, Simone; Alves Teixeira, Maraiza; Valle, Ilaria; Zaggia, Ivan; Agosti, Emanuela; Prodam, Flavia; Filigheddu, Nicoletta
Abstract: Aim: Loss of skeletal muscle is one of the main features of cancer cachexia. Vitamin D (VD) deficiency is associated with impairment of muscle mass and performance and is highly prevalent in cachectic patients; therefore, VD supplementation has been proposed to counteract cancer cachexia‐associated muscle loss. However, in both cachectic cancer patients and tumour‐bearing animals, VD supplementation led to disappointing results, urging the need for a better understanding of VD activity on skeletal muscle. Methods: Cancer‐associated muscle wasting was reproduced in vitro by treating C2C12 myotubes with cancer cell conditioned medium, a combination of TNF‐α and IFNγ or IL‐6 pro‐cachectic cytokines. The biological effects and mechanisms of action of 1, 25‐dihydroxy VD (1, 25 VD) and its precursor 25‐hydroxy VD (25 VD) on myotubes were explored. Results: We demonstrated that only 25 VD was able to protect from atrophy by activating Akt signalling, inducing protein synthesis, and stimulating the autophagic flux, while 1, 25 VD had an atrophic activity per se, increasing FoxO3 levels, inducing the expression of atrogenes, and blocking the autophagic flux. Furthermore, we showed that the contrasting activities of these VD metabolites on C2C12 myotubes depend on a differential induction of VD‐24‐hydroxylase and transformation of VD metabolites in pro‐atrophic 24‐hydroxylated products, as silencing of VD‐24‐hydroxylase reduced the atrophic activity of 1, 25 VD. Conclusions: Altogether these data might explain the lack of efficacy of VD treatment in vivo for the protection of muscle mass in cancer.